2019
DOI: 10.15537/smj.2019.1.23396
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase-3-like protein 1 levels in bipolar disorder

Abstract: Objectives: To evaluate the relationship between the expression level and biologic role of YKL-40 in bipolar disorder (BD). Methods: This case-control study was conducted in the Faculty of Medicine, Canakkale Onsekiz Mart University, Canakkale, Turkey in 2015. One hundred and four patients diagnosed as having bipolar disorder (DSM5 criteria), and 96 participants were included as healthy controls in this study. A human YKL-40 enzyme-linked immunosorbent assay (ELISA) kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Metabolic syndromes are also linked to neuroinflammation [62], which could explain increased Chil3 (chitinase-3-like protein) expression in the amygdalas of BD mice. Chil3 is produced by myeloid cells in rodents in response to neuroinflammation [63][64][65], and in humans, elevated serum levels of Chil3L1 (chitinase-3-like protein 1) have been identified in BD patients [66] and individuals with neuroinflammatory conditions [67]. However, there was no differential expression of pro-inflammatory cytokines and glial markers in the colons and amygdalas of BD mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic syndromes are also linked to neuroinflammation [62], which could explain increased Chil3 (chitinase-3-like protein) expression in the amygdalas of BD mice. Chil3 is produced by myeloid cells in rodents in response to neuroinflammation [63][64][65], and in humans, elevated serum levels of Chil3L1 (chitinase-3-like protein 1) have been identified in BD patients [66] and individuals with neuroinflammatory conditions [67]. However, there was no differential expression of pro-inflammatory cytokines and glial markers in the colons and amygdalas of BD mice.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Chil3L1 (chitinase-3-like protein 1) is expressed in several cell types including glial cells, and is involved in the inflammatory processes of the innate immune system [98]. Importantly, elevated serum levels of Chil3L1 have been identified in BD patients [99] as well as in individuals with neuroinflammatory conditions [100].…”
Section: Discussionmentioning
confidence: 99%
“…Our primary analysis identified 32 biomarkers that were associated with bipolar disorder in both cohorts. Of these, 22 are novel with respect to bipolar disorder, while serum or plasma concentrations of AM [ 32 ], CCL3 [ 33 35 ], CCL4 [ 33 , 36 ], CCL20 [ 37 ], CCL25 [ 38 , 39 ], CHI3L1 [ 40 , 41 ], GDF-15 [ 39 ], IL-10 [ 39 ], MMP-7 [ 37 ], and TNF-R1 [ 39 ] have previously been reported to be higher in patients with bipolar disorder than controls. In line with the inflammatory hypothesis of bipolar disorder [ 42 ], we report altered levels of both proinflammatory (IL-17RB, IL-12, IL-12B) and regulatory (IL-10) cytokines and receptors, as well as chemokines (CXCL16, CCL3, CCL4, CCL20, CCL25), whereof only CCL3 was suggestively associated with medication.…”
Section: Discussionmentioning
confidence: 99%
“…CHI3L1 is up-regulated in inflammatory diseases such as rheumatoid arthritis, osteoarthritis, and asthma ( Querol-Vilaseca et al, 2017 ). It is also reported that CHI3L1 is up-regulated in patients with chronic neurological disease such as Alzheimer’s disease, bipolar disorder, and schizophrenia ( Bonneh-Barkay et al, 2010 ; Choi et al, 2018 ; Sahin et al, 2019 ). In our previous studies, we found that CHI3L1 deficiency attenuates inflammation-induced liver injury, and that administration of an inhibitor of CHI3L1 restores memory by alleviating neuroinflammation in an Alzheimer’s disease mouse model ( Choi et al, 2018 ; Lee et al, 2019 ).…”
Section: Introductionmentioning
confidence: 97%